A 2007 Social Accounting Matrix for Malawi - Douillet, Mathilde; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2012)
This paper documents a Malawian Social Accounting Matrix (SAM) for the year 2007. The SAM is based on newly estimated supply-use tables, national accounts, government budgets, and balance of payments. The SAM reconciles these data using cross-entropy estimation techniques. The final SAM is a detailed representation of Malawi’s economy. It separates 37 activities and commodities; 5 types of factors of production; and 10 representative household groups. Labor and household information is drawn from a nationally representative household survey. The SAM also identifies government, investment and foreign accounts. It provides an ideal tool for economy-wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling. The 2007 SAM for Malawi was developed by the Development Strategy and Governance Division (DSGD) at IFPRI. It was partly funded by USAID as part of their support to DSGD’s Malawi Country Strategy Support Program (MaSSP).